Exoseal for puncture site closure after antegrade procedures in peripheral arterial disease patients - Hackl, Gerald (Diagn Interv Radiol, 2014)
PURPOSE: Exoseal is a vascular clo sure device consisting of a plug applier and a bio-absorbent polyglycolic acid plug available in sizes 5 F, 6 F, and 7 F. In this study, we aimed to evaluate the effectiveness and safety of the Exoseal vascular closure device (Cordis Corporation, Bridgewater, New Jersey, USA) for puncture site closure after antegrade endovascular procedures in peripheral arterial occlusive disease (PAOD) patients. MATERIALS AND METHODS: In this retrospective study, a total of 168 consecutive patients who underwent an interventional procedure due to PAOD, were included. In each case, an antegrade peripheral endovascular procedure was performed via the common femoral artery using the Seldinger technique, and Exoseal 5 F, 6 F, or 7 F was used for access site closure. The primary endpoint was a technically successful application of Exoseal. All complications at the access site within 24 hours were registered as a secondary endpoint. RESULTS: In a group of 168 patients (64.9% men, average age 71.9±11.9 years), the technical application of Exoseal was successful in 166 patients (98.8%). Within the first 24 hours after the procedure, 12 complications (7.2%) were recorded including, three pseudoaneurysms (1.8%) and nine hematomas (5.4%). None of the complications required surgical intervention. CONCLUSION: Exoseal is a safe and effective device with high technical success and acceptable complication rates for access site closure after antegrade peripheral endovascular procedures.